MG-131 ZNF259 is a candidate gene for alopecia-primordial dwarfism-renal syndrome (APDRS). (4th December 2015) - Smith, Amanda; Clericuzio, Carol; Ahmed, Afsana; McDonell, Laura; Sawyer, Sarah; Bulman, Dennis; Boycott, Kym
Abstract : APDRS is characterised by congenital alopecia, dwarfism and hypoplastic kidneys. This syndrome was observed in 5 Hispanic New Mexican children from four families. All had symmetric intrauterine growth and progressively severe postnatal growth restriction. Skin colour is very pale with a porcelain-like appearance. Affected children have a prominent forehead, deep-set eyes, downturned corners of the mouth and full cheeks. One had cleft palate, two had shunted hydrocephalus and both males had genital hypoplasia. All had severe global delays and sensorineural hearing loss. Four children died within the first two years of life, from uremia and/or sepsis. The surviving patient is a 16 yo girl with renal failure, central fat distribution and type1 diabetes. Whole exome sequencing performed on the surviving patient and her unaffected parents yielded a homozygous missense mutation at a highly conserved locus of the ZNF259 gene, both parents were carriers. Sanger sequencing of unaffected parents and siblings of a deceased patient demonstrated parents and one sibling were heterozygous carriers of the mutation. The parents of a third affected were found to be heterozygous carriers of the same mutation, patient DNA was unavailable. These results suggest a founder mutation in these families. ZNF259 encodes a zinc finger protein that has been demonstrated to play an important role in transcription, DNA synthesis and cell proliferation. Down-regulation of ZNF259 results in arrest at G1 and G2 phases of cell cycle. Western blot on patient fibroblasts demonstrated a loss of ZNF259 protein and cell cycle analysis is currently underway.